“Excorporation” and “Carnival” in Humoristic Street Actions Staged for Nonviolent Struggle: The 1996-7 Student Protests and the Resistance Movement (Otpor), Serbia - Sombatpoonsiri, Janjira (Thammasat Review, 2015)
In this paper, I seek to understand the way in which humoristic street actions operate in a nonviolent struggle by examining the extensive staging of humoristic actions during the students’ nonviolent protest in 1996-7 in Serbia, and the nonviolent movement Otpor. The concepts of “excorporation” and “carnival” are in use to understand the operation of these actions. I argue that humoristic actions are defiant because they work to emasculate the opponent’s rhetoric by appropriating and juxtaposing it with other discursive forces, for the rhetoric to be mirthful. Humoristic actions, when manifest in the form of carnival, can also be disarming and transformative. Carnival-like actions generate the positive energy which transcends the reality of pending clash between protesters and authorities. The first section discusses the relationship between nonviolence and humor presented in existing scholarship. Then, humoristic actions staged in the Serbian case are categorized and detailed. The final section, through the concepts of excorporation and carnival, analyses the operation of humoristic street action.